The Effect of Purchasing Accounting System on Transaction Efficiency and Supplier Satisfaction - Hadi, Raihan Jazil; Yadi, Amri; Hazmi, Yusri (Nomico, 2024)
This article discusses the importance of the Purchasing Accounting System in supporting business continuity, especially in the procurement of goods needed by the company. This system serves as a vital element in the company's operational cycle, which focuses on recording, managing, and tracking transactions for the purchase of goods or services. This research uses the literature study method, by collecting data from various relevant sources. The results of the analysis show that the Purchasing Accounting System consists of a series of integrated procedures, methods, and tools to ensure that every purchase transaction is recorded accurately and managed efficiently. The main components in this system include processes ranging from submission of purchase requests, evaluation and selection of suppliers, to payment of supplier invoices. With a well-structured system in place, companies can minimise errors, ensure compliance with internal policies, and manage cash flow more effectively. The system also supports transparency in supplier relationships, and improves efficiency and accuracy in the purchasing process. In short, the Purchasing Accounting System plays a crucial role in efficiently managing the purchasing aspect, which in turn supports the continuity and success of the company's operations.